Innovation in Municipal Waste Management in Malang, Indonesia - Maskur, Ali (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
This paper described explanation about innovation of waste management reflected in Waste Bank in Indonesia. Malang district was the suitable place due to the success of Malang Waste Bank (MWB) in initiating waste management innovation. Qualitative method was used in order to give clear understanding. The result showed that there are some innovations was created by waste bank like waste saving that can be used to finance daily needs such as education, groceries, health, and social activities. The bank also used information technology to record and report on customer savings. In order to maintain the sustainability, the waste bank cooperated with some stakeholders such as local government, National Electric Company, and some local waste businessman. There are several factors influencing the success of waste bank in managing waste, including: understanding of waste business networks and the ability to position itself in the business networks, supporting from local government and other agencies to conduct waste business, and involving environmental activists in the wastemanagement.